THE MAKING OF SUN FLOWERS AS THE CREATIVITY OF STKIP SINGKAWANG STUDENTS - Rika Wayuni; Melyani Melyani; Mega Selvi auliana Sari; Reza Safitri (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2019)
The management of used goods needs to be improved in order to reduce pollution and contamination. The largest source of waste comes from settlements, which 75% consists of organic waste and only 25% inorganic waste. Inorganic waste management is still very minimal. Inorganic waste is very difficult to degrade and cannot even be degraded at all naturally, therefore a very large area is needed to compensate for the production of this type of waste. One of the most common inorganic waste found in the community is a plastic straw. Plastic straws are a drinking aid that is only used occasionally and in turn, increases the amount of waste available. Plastic straw waste in Singkawang City is one of the elements causing pollution that is not easily broken down because it is made of inorganic plastic. Plastic straw waste in Indonesia reaches more than 93.2 million per day, because of its large potential, it would be better if this plastic waste is used as a product and creativity in order to organize plastic waste properly, so that plastic really supports people's economic life community.